Effect of electrospun thymol-loaded nanofiber coating on vitamin B profile of gilthead sea bream fillets (Sparus aurata) - Ceylan, Zafer; Yaman, Mustafa; Sagdic, Osman; Karabulut, Ercan; Yilmaz, Mustafa Tahsin (ELSEVIER SCIENCE BV, 2018)
The effect of electrospun chitosan-based nanofibers (CH) and thymol-loaded electrospun chitosan-based nanofibers (TCH) were investigated in terms of stability of unstable B vitamin complex during cold storage period. Scanning Electron Microscopy revealed that the average fiber diameters were determined to range between 98.12 tan and 135.94 nm. CH and TCH were both effective against loss and rapid changes of unstable B vitamin complex. 7% average change in thiamin value was observed for samples coated with TCH, but it increased up to 39% in uncoated samples. In terms of thiamin content, the positive effect of nanofiber coating for the samples coated with TCH was observed on the 11th day of storage. Average change in riboflavin for CH and TCH was found to be lower. Particularly, sharply changes in nicotinamide acid, pyridoxal, pyridoxine and pyridoxamine contents were determined for uncoated samples, as compared to slightly changes in CH and TCH. The objective of this work was to obtain nanofibers. In this sense, potential effect of nanofibers on vitamin B profiles of fish fillets was to investigate. The results revealed that coating of the fish fillets with the nanofibers could be a promising technique to keep the stability of unstable B vitamin complex.
Keywords: Biopolymer; Bioactive material; Thiamin; Riboflavin; Niacin; LIQUID-CHROMATOGRAPHIC DETERMINATION; DICENTRARCHUS-LABRAX FILLETS; CHITOSAN NANOFIBERS; THIAMINE-DEFICIENCY; NANO-ENCAPSULATION; ACID; PYRIDOXINE; FOODS; HPLC; Food Science & Technology